Evaluation of changes of cardiac morphology and function in fetuses with ductus arteriosus constriction by Speckle-tracking echocardiography - Li, Tianjing; Han, Jiancheng; Han, Yanli; Liu, Xiaowei; Gu, Xiaoyan; Zhang, Ye; Sun, Lin; Zhao, Ying; Gao, Shuang; Hao, Xiuxiu; He, Yihua (Frontiers in Pediatrics, 2023)
Background: Premature ductus arteriosus constriction (DA Con) can result in right ventricular enlargement, right ventricular hypertrophy, and tricuspid regurgitation. Method: This study retrospectively analyzed 34 singleton fetuses that underwent fetal echocardiography with a diagnosis of DA Con (16 cases with mild to moderate, and 18 cases with moderate to severe) and 45 healthy fetuses. The morphology and function parameters of cardiac, as well as the 24-Segment of ventricles, were compared between the DA Con group and controls, and between the mild to moderate and moderate to severe groups, using the fetal heart quantification (FHQ) technology. Results: There were no significant difference in left ventricular parameters in DA Con group when compared to controls. Moreover, fetal 4CV-GSI was significantly reduced, as well as the sphericity index (SI), fractional shortening (FS), global longitudinal strain (GS) and fractional area change (FAC) of right ventricle, especially in the basal-middle segments. Compared with the mild to moderate group, LV-FS increased and RV-FS decreased in moderate to severe group. Conclusion: The results showed that the fetal heart in the DA Con group was different from the controls in morphology and function. FHQ technology provides a comprehensive assessment for the evaluation of cardiac morphological and functional changes in DA Con fetuses.